Improving History Learning Activities and Outcomes through the Student Facilitator and Explaining Model Assisted by Vlogs - Kadek Ari Errawan; I Nengah Suastika; I Ketut Sedana Arta; Luh Indrayani (Universitas Pendidikan Ganesha, 2026)
This study is motivated by the low level of student activity and learning outcomes in history learning, which requires innovation in instructional models and media to be more interactive. The aim of this study is to analyze the effect of implementing the Student Facilitator and Explaining (SFE) learning model assisted by vlog media on student activity and learning outcomes. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The population consisted of 248 students, with a sample of 60 students selected purposively and divided into an experimental group and a control group. Data were collected through learning outcome tests, student activity questionnaires, and observation sheets. Data analysis was conducted using an independent t-test and regression analysis. The results showed a significant improvement in learning outcomes in the experimental group compared to the control group (t = 3.85; p < 0.05). In addition, learning activity was found to have a significant effect on learning outcomes (R² = 0.57; β = 0.755; p < 0.05). The conclusion of this study indicates that the implementation of the SFE model assisted by vlog media is effective in improving student activity and learning outcomes. The implication is that this model and media can serve as an innovative alternative in history learning that promotes active student engagement.